How the Bible is written - Rendsburg, Gary A. (Hendrickson Publishers, 2019)
"A book focusing on the nexus between language and literature in the Bible, with specific attention to how the former is used to create the latter; topics include wordplay, wordplay with proper names, alliteration, repetition with variation, dialect representation, intentionally confused language, marking closure, and more"--